2016
DOI: 10.1155/2016/2349712
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Strategies for Maximum-Flow Problem in Uncertain Decentralized Systems Using Reliability Analysis

Abstract: This study investigates a multiowner maximum-flow network problem, which suffers from risky events. Uncertain conditions effect on proper estimation and ignoring them may mislead decision makers by overestimation. A key question is how self-governing owners in the network can cooperate with each other to maintain a reliable flow. Hence, the question is answered by providing a mathematical programming model based on applying the triangular reliability function in the decentralized networks. The proposed method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In financial networks, Eboli [17] has described the balance-sheet as a loss flow on the arc. e time-varying maximum flow problem (TMFP) [18,19] and wastage maximum flow problem (WMFP) [20] have been investigated extensively. Li and Buzdalov et al [21,22] proposed their algorithms for solving the TMFPs.…”
Section: Introductionmentioning
confidence: 99%
“…In financial networks, Eboli [17] has described the balance-sheet as a loss flow on the arc. e time-varying maximum flow problem (TMFP) [18,19] and wastage maximum flow problem (WMFP) [20] have been investigated extensively. Li and Buzdalov et al [21,22] proposed their algorithms for solving the TMFPs.…”
Section: Introductionmentioning
confidence: 99%
“…Their research demonstrated that powerful maximum flow algorithm can be developed using borrowed or new techniques, thus departing from finding maximum flow using augmenting path and residual path concepts. Gharehbolagh et al (2016) proposed a maximum flow optimization model that incorporated reliability analysis. Application of reliability in maximum flow networks helps the decision makers to make better decisions.…”
Section: Motivationmentioning
confidence: 99%
“…Heidari Gharehbolagh et al (2016) proposed a mathematical programming model based on triangular reliability function to maintain reliability of flow in decentralized networks to examine how self-governing owners can cooperate with each other.…”
Section: Reliability Analysismentioning
confidence: 99%